CONTROL SYSTEM OF THE ELECTRICAL COMPLEX OF STREET LIGHTING - SINCHUK, Oleg; GORSHKOV, Victor (Herald of Khmelnytskyi National University. Technical sciences, 2022)
To date, taking into account the strategies for the development of control systems and the active introduction of distributed generation sources into various spheres of the world economy, including those based on renewable sources of electrical energy, hybrid systems of artificial outdoor lighting controlled by intelligent control systems are being developed. The paper proposes an approach to the construction of an external lighting control system on city highways and public places. Regulation of external lighting is carried out by adjusting the luminous flux of lamps, and the sources of luminous flux are the lamps with which they are equipped. But not all types of lamps are suitable for adjusting the smooth change of light flux. If there is a communication channel between the network of lamps equipped with EIDs and the dispatching service, it is possible to transmit information about the state of operation of EIDs and the performance of lamps in order to detect deviations in the operation of EIDs and lamps that need to be replaced. In accordance with the given schedule for changing the level of external lighting, the KD software sends a command to change the level of light flux on specific lamps. The control unit transmits incoming information (a command) to the control unit, which, together with the lamp control channel connected to it, forms a local lighting control network. The decentralized outdoor lighting control system provides for the absence of a control room, server, server access devices, as well as the Internet as a means of communication, executive equipment of the substation and replacement of the PUS with the APUS, as well as the presence of service personnel who will service the equipment of the APUS substation, KOP and SC, as a result of the lack of feedback from the APUS to the OP, i.e. the maintenance of the PS is carried out directly by maintenance and programming specialists Thus, a scheme for decentralized management of outdoor lighting on city highways and public places was proposed.